1,4-Bis(iodomethyl)benzene - McAdam, C. John (International Union of Crystallography, 2009)
The centrosymmetric title compound, C(8)H(8)I(2), was prepared by metathesis from the dibromo analogue. In the crystal structure, weak C—H⋯I interactions link the molecules into stacks down the b axis. The structure is further stabilized by short I⋯I contacts [3.8433 (2) Å], forming undulating sheets in the (101) plane.